2012
DOI: 10.5897/ijps10.564
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the machining parameters of AISI D2 tool steel material with multi wall carbon nano tube in electrical discharge machining process using response surface methodology

Abstract: This work investigates the machining characteristics of American Iron and Steel Institute (AISI) D2 tool steel with copper as a tool electrode during electrical discharge machining (EDM) process. The multi wall carbon nano tube (MWCNT) is mixed with dielectric fluids in EDM process to analyze the surface characteristics of surface roughness. Regression model were developed to predict the surface roughness (SR) in EDM process. In the development of predictive models, machining parameters of pulse current, pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…High resistance to corrosion abrasion surface is produced by PMEDM process [3][4][5]. So many research works was [8,[11][12][13][18][19][20][21]23,25,26,36,37]. In spite of the improved results, practical application of NPMEDM in industry is very low rate.…”
Section: Abbreviationsmentioning
confidence: 99%
“…High resistance to corrosion abrasion surface is produced by PMEDM process [3][4][5]. So many research works was [8,[11][12][13][18][19][20][21]23,25,26,36,37]. In spite of the improved results, practical application of NPMEDM in industry is very low rate.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Wong et al 22 utilized crushed glass as an additive to machine AISI-01, SKH 54 tool steels and found no significant effect of it on both MRR and surface quality due to its very poor electrical and thermal conductivities. Sari et al 20 and Prabhu and colleagues 4851,5356 concluded that carbon nanotubes (CNTs) mixed in the dielectric resulted in huge improvement of MRR compared to other powder materials. This phenomenon was attributed to the low density and high thermal conductivity of CNT.…”
Section: Influence Of Powder Properties On Machining Characteristicsmentioning
confidence: 99%
“…The most influencing factor in this study was found to be discharging current [6]. Another notable study by Prabhu and Vinayagam [7] was on the modelling and characterization of EDM process parameters of AISI D2 toll steel material with multiwall carbon nanotubes and developed the prediction of SR as response parameter and pulse current, pulse duration, and pulse voltage as model variables with copper electrode using Box-Behnken in RSM. Li and Lee [8] studied the different optimal machining parameters (voltage, discharge current, pulse on time, and flushing pressure) setting and electrode polarity (copper tungsten electrode) on response parameter MRR and SR by implementing RSM.…”
Section: Introductionmentioning
confidence: 99%